Glass scattering prevention sheet
By introducing deformation properties and controlling peeling properties into the adhesive layer, the problems of scattering and sticking and slipping of glass fragments in the prior art are solved, and a more efficient scattering prevention effect is achieved.
Patent Information
- Application Number
- CN202010896261.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-06
- Filing Date
- 2020-08-31
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-08-31
Smart Images

Figure CN112457788B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a glass scattering prevention sheet used to be attached to a cover glass of a mobile device. Background Art
[0002] Most mobile devices (smartphones, tablet terminals, etc.) have a capacitive touch panel cover glass on the visual recognition side surface. If a mobile device of this structure is subjected to a large impact due to falling or the like, the cover glass will break and glass fragments will fly around. Therefore, in order to prevent the glass fragments from scattering when the cover glass breaks, it is proposed to attach a scattering prevention sheet with an adhesive layer to the surface (touch surface side) and the back side (non-touch surface side) of the cover glass (for example, Patent Documents 1 and 2). It should be noted that when the scattering prevention sheet is attached to the non-touch surface side, it is sometimes also referred to as an inner patch (Patent Document 2).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 2011-168652
[0006] Patent Document 2: Japanese Patent Application Laid-Open No. 2016-162284 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, the conventional sheets provided with an adhesive layer such as the technologies of Patent Documents 1 and 2 are not sufficiently capable of preventing glass fragments from scattering when a mobile device is dropped and the cover glass is broken, and improvement is required.
[0009] One aspect of the present invention is to provide a glass scattering prevention sheet having improved performance in preventing scattering of glass fragments.
[0010] Solutions to Solve Problems
[0011] The present inventors believed that if the adhesive layer of the cover glass sheet attached to the mobile device is given deformation performance, that is, the performance of following the large force applied to the mobile device instantly when it falls to the ground, the performance of preventing the scattering of glass fragments can be improved compared with the past. And it was found that with respect to the deformation performance (that is, the performance of being able to follow when a large force is applied instantly), by controlling the "peeling performance" of the adhesive layer, specifically, by constituting the adhesive layer in a manner that "when peeled off from the object after bonding at a high speed, it can be peeled off without causing a stick-slip phenomenon", the scattering prevention performance can be improved, thereby completing the present invention.
[0012] Furthermore, the inventors have found that further improvement in the scattering prevention performance can be expected if the "viscous-elastic properties at high frequencies (100 Hz)" of the pressure-sensitive adhesive layer are controlled.
[0013] That is, the glass scattering prevention sheet of the present invention is characterized in that it is a sheet attached to the cover glass of a mobile device (particularly the cover glass of a capacitive touch panel arranged on the visual recognition side surface of the mobile device) to prevent the scattering of glass fragments when the cover glass is broken.
[0014] The sheet comprises a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer composed of a pressure-sensitive adhesive composition on one surface of a film substrate.
[0015] Under an environment of temperature 23°C and relative humidity 50%, the adhesive layer of the adhesive sheet was attached to a 3mm thick glass using a roller with a load of 2kgf. After 30 minutes, the adhesive sheet was peeled off from the glass at a high speed along a 180-degree direction at a speed of 30,000mm / min. The peeling was able to be performed without causing stick-slip phenomenon.
[0016] In the glass scattering prevention sheet of the present invention, the loss tangent (tan δ) of the pressure-sensitive adhesive layer at a frequency of 100 Hz can be adjusted to be 1.26 or less.
[0017] In the glass scattering preventing sheet of the present invention, the adhesive composition constituting the adhesive layer may include a crosslinking agent and a (meth)acrylate polymer including a structural unit derived from butyl acrylate.
[0018] The glass scattering prevention sheet of the present invention may include a functional layer on the surface of the film substrate on which the adhesive layer is not formed, and the functional layer may have printability.
[0019] Effects of the Invention
[0020] The glass scattering prevention sheet of the present invention is configured so as to be peelable without causing a stick-slip phenomenon during high-speed peeling, and thus can improve the glass fragment scattering prevention performance compared to conventional sheets. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a cross-sectional view of a glass scattering prevention sheet according to one embodiment of the present invention.
[0022] Figure 2 It is a cross-sectional view showing a configuration example of a touch panel.
[0023] Figure 3 This is a schematic diagram of a block-shaped test piece used in the characteristic evaluation (impact resistance test) of the examples.
[0024] Figure 4 For application Figure 3Schematic diagram of the test equipment for the block test piece.
[0025] Figure 5 for Figure 4 An enlarged view of the portion surrounded by the dot-dash line. DETAILED DESCRIPTION
[0026] Hereinafter, embodiments of the present invention will be described.
[0027] [Glass scattering prevention sheet]
[0028] like Figure 1 As shown, a glass scattering prevention sheet 1 according to one embodiment of the present invention includes an adhesive sheet having an adhesive layer 11 composed of an adhesive composition on one surface of a film substrate 12, and the glass scattering prevention sheet is attached to a cover glass of a capacitive touch panel arranged on a visual recognition side surface of a mobile device.
[0029] There are various configurations of a capacitive touch panel, and a typical example thereof includes a display module such as a liquid crystal module, a film sensor stacked on the module, and a cover glass stacked on the sensor.
[0030] In the present invention, the glass scattering prevention sheet can be attached to the outer surface (touch surface) of the cover glass as an external sheet of the mobile device, or can be attached to the inner surface (non-touch surface, such as between the film sensor and the cover glass) of the cover glass as an internal sheet of the mobile device. Figure 2 )'s inner surface (non-contact surface).
[0031] The glass scattering prevention sheet 1 of the present embodiment is characterized in that, under an environment of a temperature of 23°C and a relative humidity of 50%, the adhesive layer 11 surface of the adhesive sheet constituting the sheet is bonded to a glass having a thickness of 3 mm using a roller with a load of 2 kgf, and after 30 minutes, the adhesive sheet is peeled off from the glass at a high speed in a direction of 180 degrees at a speed of 30,000 mm / min, and the peeling can be performed without causing a stick-slip phenomenon.
[0032] The inventors have found that when the stick-slip phenomenon occurs under this condition, when the mobile device hits the ground due to being dropped, the adhesive sheet (the adhesive layer 11) is peeled off from the cover glass, and as a result, the scattering of glass fragments of the broken cover glass cannot be completely prevented. In other words, we believe that the reason why the adhesive sheet (the adhesive layer 11) is peeled off from the cover glass under this condition is that the adhesive layer cannot deform (follow) when a large force is applied to the mobile device in an instant.
[0033] The adhesive layer 11 of the adhesive sheet constituting the glass scattering prevention sheet 1 of the present embodiment is a viscoelastic body having both viscous properties and elastic properties. A viscous body having a viscous property has the following property: the higher the deformation speed (impact speed), the less likely it is to deform. On the other hand, a perfect elastic body having only elastic properties has the following property: even if the deformation speed increases, the energy related to the deformation does not change, and the deformation can be achieved.
[0034] It is considered that in the case of an adhesive layer in which the elastic part and the sticky part are randomly present in the adhesive layer, the elastic part is large (e.g., more than 80% of the whole) and the sticky part is small (e.g., less than 20% of the whole), the adhesive layer will deform, and when a large force is applied instantly, strain will occur in the adhesive layer due to the difference in deformability, thereby causing peeling. That is, in order to reduce the deformability of the elastic part and the sticky part randomly present inside, the ratio of the elastic part to the sticky part of the adhesive layer 11 constituting the glass scattering prevention sheet 1 of the present embodiment is preferably, for example, 45:55 to 55:45.
[0035] The present invention configures the adhesive layer of the adhesive sheet to have such a deformability, and as a result, it is possible to completely prevent the scattering of glass fragments of a broken cover glass.
[0036] In the present invention, "stick-slip" refers to the following phenomenon: for example, as shown in the adhesion-peel time curve when measuring under the conditions of the 180-degree peel adhesion measurement test on a test plate described in JIS-Z0237, the adhesion force is maintained at a certain maximum value for a certain period of time, the adhesion force is rapidly reduced, and then the adhesion force is immediately restored, while gradually peeling off.
[0037] "No stick-slip phenomenon" means that the amplitude of the maximum adhesive force does not increase or decrease by 30% or more repeatedly (twice or more). When the amplitude of the adhesive force is less than 30%, it is a continuous peeling state, which is not considered as peeling due to "stick-slip".
[0038] The glass scattering prevention sheet 1 of the present embodiment preferably has the above-mentioned performance and the loss tangent (tanδ) of the adhesive layer 11 of the adhesive sheet at a frequency of 100 Hz adjusted to 1.26 or less, preferably 1.23 or less. The present inventors have also found that if the viscoelasticity at a high frequency (100 Hz), specifically tanδ, is 1.26 or less, while being able to be peeled without causing a stick-slip phenomenon, further improvement in scattering prevention performance can be expected.
[0039] The pressure-sensitive adhesive layer 11 of the present embodiment having the above-described properties is composed of a pressure-sensitive adhesive composition containing a pressure-sensitive adhesive component.
[0040] The adhesive component preferably contains a (meth)acrylate polymer as a main polymer. (Meth)acrylate refers to both acrylate and methacrylate. The same applies to other similar terms. In addition, "polymer" also includes the concept of "copolymer".
[0041] The (meth)acrylate polymer preferably contains, as a monomer constituting the polymer, an alkyl (meth)acrylate having an alkyl group with a carbon number of 1 to 20. This allows the obtained adhesive to exhibit preferred adhesiveness.
[0042] The (meth)acrylate polymer may also be composed of a copolymer of a (meth)acrylate alkyl ester having an alkyl group with 1 to 20 carbon atoms, a monomer having a reactive functional group (a monomer containing a reactive functional group), and other monomers used as desired. The (meth)acrylate polymer contains a monomer containing a reactive functional group as a monomer constituting the polymer, thereby reacting with a crosslinking agent to form a crosslinked structure.
[0043] Examples of (meth)acrylic acid alkyl esters having an alkyl group with 1 to 20 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, and stearyl (meth)acrylate. Among them, from the viewpoint of easy adjustment of the glass transition temperature, (meth)acrylic acid alkyl esters having 1 to 8 carbon atoms are preferred, and methyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are more preferred. These may be used alone or in combination of two or more.
[0044] In particular, by using a (meth)acrylate polymer containing at least a structural unit derived from n-butyl acrylate (BA), it is easy to adjust the adhesive so as not to cause a stick-slip phenomenon during high-speed peeling.
[0045] The (meth)acrylate polymer preferably contains at least (more than 0% by mass) 100% by mass or less, more preferably 20% to 80% by mass, of an alkyl (meth)acrylate having an alkyl group with 1 to 20 carbon atoms as a monomer unit constituting the polymer.
[0046] As the monomer containing a reactive functional group, preferably, there are: a monomer having a hydroxyl group in the molecule (a hydroxyl group-containing monomer), a monomer having a carboxyl group in the molecule (a carboxyl group-containing monomer), a monomer having an amino group in the molecule (an amino group-containing monomer), etc. Among them, a hydroxyl group-containing monomer is particularly preferred. These monomers containing reactive functional groups may be used alone or in combination of two or more.
[0047] Examples of hydroxyl-containing monomers include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Among them, 2-hydroxyethyl (meth)acrylate is preferred from the perspective of the hydroxyl group in the obtained (meth)acrylate polymer, the reactivity with the crosslinking agent, and the copolymerizability with other monomers. These may be used alone or in combination of two or more.
[0048] Examples of carboxyl-containing monomers include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. Of these, acrylic acid is preferred from the perspective of the reactivity of the carboxyl group in the obtained (meth)acrylate polymer (A), the reactivity with the crosslinking agent, and the copolymerizability with other monomers. These may be used alone or in combination of two or more.
[0049] Examples of the amino group-containing monomer include aminoethyl (meth)acrylate, n-butylaminoethyl (meth)acrylate, etc. These may be used alone or in combination of two or more.
[0050] As for the (meth)acrylate polymer, from the viewpoint of crosslinking, as the monomer unit constituting the polymer, it is preferred to contain a monomer containing a reactive functional group (particularly a hydroxyl group-containing monomer). The hydroxyl value of the monomer containing a reactive functional group is preferably 1 mgKOH / g or more and 80 mgKOH / g or less, and more preferably 5 mgKOH / g or more and 50 mgKOH / g or less.
[0051] Regarding the (meth)acrylate polymer, other monomers that may be contained as monomers constituting the polymer include, for example: (meth)acrylate alkoxyalkyl esters such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; non-crosslinking acrylamides such as acrylamide and methacrylamide; (meth)acrylates having non-crosslinking tertiary amino groups such as N,N-dimethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate; vinyl acetate; styrene, etc. These may be used alone or in combination of two or more.
[0052] The (meth)acrylate polymer may be polymerized in a random copolymer or a block copolymer.
[0053] The weight average molecular weight (Mw) of the (meth)acrylate polymer is preferably 300,000 to 600,000, more preferably 400,000 to 600,000. When the weight average molecular weight is less than 300,000, there is a risk of cohesive failure. On the other hand, when the weight average molecular weight exceeds 600,000, there is a risk of insufficient adhesion. It should be noted that the weight average molecular weight is a value converted to polystyrene measured by gel permeation chromatography (GPC).
[0054] The weight average molecular weight can be measured, for example, under the following measurement conditions.
[0055] Chromatographic columns: "TSK-gel superHZM-M", "TSK-gel HZM-M", "TSK-gel HZ2000"
[0056] Eluent: THF
[0057] Flow rate: 0.35mL / min
[0058] Injection volume: 10 μL
[0059] Column temperature: 40°C
[0060] Detector: UV-8020
[0061] The glass transition temperature (Tg) of the (meth)acrylate polymer is preferably -70°C to 0°C. When Tg is less than -70°C, there is a risk of insufficient cohesion (Japanese: aggregation force). On the other hand, when Tg exceeds 0°C, there is a risk of not showing adhesion. From the viewpoint of achieving a balance between adhesion, viscosity, and cohesion, the Tg of the main polymer is more preferably -40°C to -15°C. It should be noted that the Tg of the main polymer is a value calculated by the following relationship between the glass transition temperature Tg (°C) of the main polymer based on the FOX formula.
[0062] 1 / (273+Tg)=Σ{Wi / (273+Tgi)}
[0063] In the above formula, "Wi" is the mass percentage of monomer i, and "Tgi" is the Tg (°C) of the homopolymer of monomer i. It should be noted that the glass transition temperature of the homopolymer can use the value recorded in "Polymer Handbook 4th Edition John Wiley & Sons". The glass transition temperature of the homopolymer of the monomer not recorded in the above literature can be the peak temperature of the loss tangent (tanδ) obtained by dynamic viscoelasticity measurement.
[0064] In the pressure-sensitive adhesive component, the (meth)acrylate polymer may be used alone or in combination of two or more.
[0065] The adhesive component preferably contains a crosslinking agent. When the adhesive component contains a crosslinking agent and a (meth)acrylate polymer containing a monomer unit containing a reactive functional group as a constituent polymer, if the adhesive composition containing the adhesive component is heated, the crosslinking agent reacts with the reactive functional group of the monomer containing a reactive functional group constituting the (meth)acrylate polymer. Thus, a structure crosslinked with the (meth)acrylate polymer is formed by the crosslinking agent, and the cohesive force of the obtained adhesive is improved.
[0066] As a crosslinking agent, any substance that reacts with the reactive functional group possessed by the (meth) acrylate polymer may be used, and examples thereof include isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, ammonium salt crosslinking agents, etc. When the (meth) acrylate polymer has a hydroxyl group as a reactive functional group, among the above, an isocyanate crosslinking agent having excellent reactivity with the hydroxyl group is preferably used. One type of crosslinking agent may be used alone, or two or more types may be used in combination.
[0067] Examples of the epoxy crosslinking agent include ethylene glycol diglycidyl ether, etc. Among them, N,N,N',N'-tetraglycidyl-m-xylylenediamine is preferred.
[0068] The isocyanate crosslinking agent contains at least a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate; aliphatic polyisocyanates such as hexamethylene diisocyanate, alicyclic polyisocyanates such as isophorone diisocyanate, and hydrogenated diphenylmethane diisocyanate; and their biuret bodies, isocyanurate bodies, and adducts thereof as reaction products with low molecular weight active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil.
[0069] Among them, trimethylolpropane-modified aromatic polyisocyanates, particularly trimethylolpropane-modified xylylene diisocyanate and trimethylolpropane-modified toluene diisocyanate are preferred from the viewpoint of reactivity with hydroxyl groups.
[0070] The proportion of the crosslinking agent varies depending on the type of the crosslinking agent, the number of functional groups, etc., and is therefore not particularly limited. For example, the range of 0.04 to 5.0 parts by mass is preferred relative to 100 parts by mass of the (meth)acrylate polymer. By setting the proportion of the crosslinking agent to 0.04 parts by mass or more, cohesive failure is less likely to occur, and by setting it to 5.0 parts by mass or less, it is suitable in terms of easy adjustment of the adhesive force.
[0071] The adhesive composition may contain various additives as desired, such as a silane coupling agent, a refractive index adjuster, an antistatic agent, a tackifier, an antioxidant, an ultraviolet absorber, a light stabilizer, a softener, a filler, and the like.
[0072] For example, from the viewpoint of improving the adhesive strength of the obtained adhesive, it is preferred to contain a silane coupling agent. As the silane coupling agent, an organosilicon compound having at least one alkoxysilyl group in the molecule, good compatibility with the adhesive component, and light transmissiveness is preferred.
[0073] Examples of the silane coupling agent include: silicon compounds containing polymerizable unsaturated groups such as vinyl trimethoxysilane, vinyl triethoxysilane, and methacryloxypropyl trimethoxysilane; silicon compounds having epoxy structures such as 3-glycidoxypropyl trimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane; and silicon compounds containing mercapto groups such as 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, and 3-mercaptopropyl dimethoxymethylsilane. Compounds; amino-containing silicon compounds such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane; 3-chloropropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane; or condensates of at least one of these with alkyl-containing silicon compounds such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane. These may be used alone or in combination of two or more.
[0074] The content of the silane coupling agent in the adhesive composition is preferably 0.05 to 1.5 parts by mass, more preferably 0.07 to 1.0 parts by mass, based on 100 parts by mass of the adhesive component.
[0075] The adhesive composition can be produced by mixing an adhesive component and additives used as desired. When the adhesive component contains a (meth)acrylate polymer, the (meth)acrylate polymer is first prepared and then a crosslinking agent is added as desired.
[0076] The (meth)acrylate polymer can be produced by polymerizing a mixture of monomer units constituting the polymer using a conventional free radical polymerization method. The polymerization of the (meth)acrylate polymer can be carried out by a solution polymerization method or the like using a polymerization initiator as desired. Examples of the polymerization solvent include ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, and the like, and two or more thereof can be used in combination.
[0077] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more thereof may be used in combination. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].
[0078] Examples of the organic peroxide include benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl) peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, bis(3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide.
[0079] In addition, in the above-mentioned polymerization step, the weight average molecular weight of the obtained polymer can be adjusted by adding a chain transfer agent such as 2-mercaptoethanol.
[0080] After obtaining the (meth)acrylate polymer, a crosslinking agent and an additive are added to the solution of the (meth)acrylate polymer as desired, and the mixture is thoroughly mixed to obtain a pressure-sensitive adhesive composition (coating solution) diluted with a solvent.
[0081] As the diluting solvent for diluting the adhesive composition to prepare the coating solution, for example, aliphatic hydrocarbons such as hexane, heptane, and cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as dichloromethane and vinyl chloride; alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol; ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; cellosolve-based solvents such as ethyl cellosolve, etc. can be used.
[0082] The concentration and viscosity of the coating solution prepared in this way are not particularly limited as long as they are within the range that can be coated, and can be appropriately selected according to the situation. For example, the adhesive composition is diluted in a manner that the concentration reaches 10 to 40% by mass. It should be noted that when obtaining the coating solution, the addition of a diluting solvent is not a necessary condition, and if the adhesive composition has a viscosity that can be coated, the diluting solvent may not be added.
[0083] The adhesive layer 11 of the present embodiment is formed by the above-mentioned adhesive composition, specifically, by applying a coating solution of the adhesive composition to a desired material (a release sheet, a film substrate of a glass scattering prevention sheet, etc.) and curing (crosslinking). The adhesive layer 11 can be obtained by drying the adhesive composition after coating, preferably by heat treatment to cure it. After the heat treatment, a aging period of about 7 to 14 days at room temperature (e.g., 23° C., 50% RH) can be set as needed.
[0084] As a method for applying the coating solution of the adhesive composition, for example, a bar coating method, a knife coating method, a roll coating method, a blade coating method, a die coating method, a gravure coating method, etc. can be used.
[0085] The adhesive composition can be dried by air drying, and is usually dried by heating (preferably hot air drying). When the heating treatment is performed, the heating temperature is preferably 90 to 110° C. The heating time is preferably 120 seconds to 4 minutes.
[0086] When the adhesive component of the adhesive composition contains a (meth)acrylate polymer and a crosslinking agent, the (meth)acrylate polymer is crosslinked by the crosslinking agent to form a crosslinked structure by drying (heat treatment) the adhesive composition.
[0087] The thickness of the adhesive layer 11 is not particularly limited, and can be appropriately selected according to the material of the substrate. Specifically, it is preferably 0.5 μm to 50 μm, and more preferably 5 to 30 μm.
[0088] The film substrate 12 can be any material as long as it has a strength sufficient to prevent the glass from scattering when the cover glass of the touch panel is broken and is formed of a material with high optical transparency. It is usually composed mainly of a plastic film and may be composed only of a plastic film, or it may be a film substrate having a desired functional layer formed on the surface of the plastic film opposite to the adhesive layer 11.
[0089] Examples of the plastic film include transparent films made of materials such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polystyrene, triacetyl cellulose, and acrylics. Among these, a stretched, particularly biaxially stretched polyethylene terephthalate film is preferred because of its excellent mechanical strength and dimensional stability.
[0090] Examples of the functional layer include a hard coat layer, an antireflection layer, an antiglare layer, an easy-slip layer, an antistatic layer, etc. In particular, in order to impart design to the visual recognition side (cover glass) of the mobile device, at least a layer having printability may be provided.
[0091] The thickness of the film substrate 12 is usually 6 to 500 μm, preferably 23 to 200 μm.
[0092] As a manufacturing example of the adhesive sheet of the present embodiment, first prepare a release sheet, and the surface of the release sheet in contact with the adhesive layer 12 has been subjected to a release treatment. As the release sheet, for example, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polyethylene naphthalate film, polybutylene terephthalate film, polyurethane film, ethylene vinyl acetate film, ionomer resin film, ethylene (methyl) acrylic acid copolymer film, ethylene (methyl) acrylic acid ester copolymer film, polystyrene film, polycarbonate film, polyimide film, fluororesin film, etc. can be used. In addition, these cross-linked films can also be used. In addition, these laminated films can be used.
[0093] Examples of the release agent used in the release treatment include alkyd-based, silicone-based, fluorine-based, unsaturated polyester-based, polyolefin-based, and wax-based release agents.
[0094] The thickness of the release sheet is not particularly limited, but is usually about 20 to 150 μm.
[0095] The coating liquid of the adhesive composition is applied to the release surface of the prepared release sheet, and heat-treated to cure (crosslink) the coating layer, and then the film substrate 12 is attached to the coating layer. When an aging period is required, the aging period is set, and when the aging period is not required, the coating layer directly becomes the adhesive layer 11 to obtain an adhesive sheet, thereby obtaining the glass scattering prevention sheet 1 of the present embodiment.
[0096] By using the obtained glass scattering prevention sheet 1 of the present embodiment, for example, Figure 2 The capacitive touch panel 2 is shown.
[0097] [Capacitive touch panel]
[0098] The touch panel 2 of this embodiment includes a display body module 26, a film sensor 24 laminated thereon via an adhesive layer 25, a glass scattering prevention sheet 1 of this embodiment laminated thereon via an adhesive layer 23 (the peeling sheet has been peeled off), and a cover glass 21 with a patterned transparent conductive film 22 laminated via the adhesive layer 11 of the sheet 1.
[0099] That is, in the touch panel 2 , the glass scattering preventing pressure-sensitive adhesive sheet 1 is provided as an inner sheet on the back side (display module 26 side) of the cover glass 21 .
[0100] In the touch panel 2 of the present embodiment, the transparent conductive film 22 is provided on the cover glass 21 , but the transparent conductive film 22 may be provided at another location.
[0101] Examples of the display module 26 include a liquid crystal (LCD) module, a light emitting diode (LED) module, and an organic electroluminescence (organic EL) module.
[0102] The adhesive layers 23 and 25 may be formed of a desired adhesive or adhesive sheet, and may be formed of the same adhesive as the adhesive layer 11 of the anti-scattering adhesive sheet 1 .
[0103] Examples of the above-mentioned desirable adhesive include acrylic adhesives, rubber adhesives, silicone adhesives, urethane adhesives, polyester adhesives, and polyvinyl ether adhesives. Among them, acrylic adhesives are preferred.
[0104] The film sensor 24 is generally composed of a base film 241 and a patterned transparent conductive film 242. As the base film 241, for example, polyethylene terephthalate film, polyethylene naphthalate film, polycarbonate film, polymethyl methacrylate film, triacetyl cellulose film, polypropylene film, etc. can be used.
[0105] As the transparent conductive film 242, for example, transparent conductive films including metals such as platinum, gold, silver, copper, oxides such as tin oxide, indium oxide, cadmium oxide, zinc oxide, zinc dioxide, tin-doped indium oxide (ITO), zinc oxide-doped indium oxide, fluorine-doped indium oxide, antimony-doped tin oxide, fluorine-doped tin oxide, aluminum-doped zinc oxide and other complex oxides, chalcogenides, lanthanum hexaboride, titanium nitride, titanium carbide and other non-oxidizing compounds can be listed, among which a transparent conductive film including ITO is preferred.
[0106] The transparent conductive film 242 of the film sensor 24 of the touch panel 2 is Figure 2 The sensor 24 is located on the upper side of the membrane sensor 24 , but may also be located on the lower side of the membrane sensor 24 .
[0107] The glass material of the cover glass 21 is not particularly limited, and examples thereof include chemically strengthened glass, alkali-free glass, quartz glass, soda-lime glass, glass containing barium and strontium, aluminosilicate glass, lead glass, borosilicate glass, barium borosilicate glass, etc. A desired functional layer (such as a hard coating layer, etc.) may be provided on the surface of the cover glass 21.
[0108] The thickness of the cover glass 21 is not particularly limited, but is usually 0.5 to 2.0 mm, preferably 0.7 to 1.5 mm.
[0109] In the touch panel 2 of the present embodiment, a transparent conductive film 22 is patterned on the cover glass 21. As the material of the transparent conductive film 22, the same material as the transparent conductive film 242 of the film sensor 24 can be used. It should be noted that, generally, one of the transparent conductive film 22 and the transparent conductive film 242 of the film sensor 24 constitutes a circuit pattern in the X-axis direction, and the other constitutes a circuit pattern in the Y-axis direction.
[0110] When manufacturing the touch panel 2, the release sheet of the scattering prevention sheet 1 is peeled off, and the exposed adhesive layer 11 is attached to the transparent conductive film 22 provided on the back side of the cover glass 21. Then, the touch panel 2 can be manufactured by a conventional method using the cover glass 21 with the scattering prevention sheet 1.
[0111] In the touch panel 2 , even if the cover glass 21 is broken due to a large impact caused by being dropped or the like, the scattering prevention sheet 1 affixed to the cover glass 21 prevents glass fragments from scattering.
[0112] [Example]
[0113] The present invention is further described below by way of examples. It should be noted that "parts" and "%" are by weight unless otherwise specified.
[0114] 1. Production of glass scattering prevention sheet
[0115] [Experimental Example 1]
[0116] The (meth)acrylate polymer was prepared by polymerizing n-butyl acrylate. The (meth)acrylate polymer had a polystyrene-equivalent weight average molecular weight (Mw) of 450,000 as measured by gel permeation chromatography (GPC) (GPC measurement), and a glass transition temperature (Tg) of -40°C as determined by the FOX formula (described above).
[0117] 0.99 parts by mass of an epoxy crosslinking agent was added to 100 parts by mass (in terms of solid content) of the obtained (meth)acrylate polymer, and the mixture was diluted with a solvent and stirred sufficiently to obtain a coating solution of a pressure-sensitive adhesive composition.
[0118] The formulations of the adhesive compositions including the experimental examples described below are shown in Table 1. The details of the abbreviations described in Table 1 are as follows.
[0119] BA: n-butyl acrylate
[0120] 2EHA: 2-Ethylhexyl acrylate
[0121] EA: Ethyl acrylate
[0122] As a film substrate, a 50 μm thick transparent PET film (Lumirror: Toray Industries, Inc., not subjected to mold release treatment) was used, and the coating solution of the obtained adhesive composition was applied to one side thereof by a bar coating method, and then heat-treated at 100° C. for 3 minutes to form a coating film layer (adhesive layer) of the adhesive composition. Thereafter, the film was aged at 23° C. and 50% RH for 7 days to form an adhesive layer with a thickness of 25 μm, thereby obtaining a sheet sample (glass scattering prevention sheet).
[0123] [Experimental Examples 2 to 6]
[0124] Sheet samples were prepared in the same manner as in Experimental Example 1 except that the composition and weight average molecular weight of each monomer constituting the (meth)acrylate polymer, and the type and amount of the crosslinking agent used were changed as shown in Table 1.
[0125] It should be noted that, regarding Experimental Examples 5 and 6, the composition and Mw of each monomer constituting the (meth)acrylate polymer (main polymer), and the type and amount of the cross-linking agent used are the same in terms of composition (2EHA / EA), Mw (500,000), type (isocyanate system), and amount (0.40), respectively. The two experimental examples differ in the Tg of the main polymer.
[0126] 2. Evaluation
[0127] The sheet samples obtained in each experimental example were evaluated for the following items.
[0128] (2-1) Sticky
[0129] Using the sheet samples prepared in each experimental example, a sheet test piece of 25 mm wide × 250 mm long was prepared. Then, under an environment of 23°C and 50% RH, the adhesive layer of the sheet test piece was bonded to a glass of 3 mm thickness using a roller with a load of 2 kgf. After 30 minutes, the film substrate end (free portion) of the sheet test piece was folded back 180 degrees from the glass and continuously peeled at a tensile speed of 30,000 mm / min. The peel strength at this time (180-degree peeling adhesive force relative to the peeling time. Unit: N / 25 mm) was measured, and the occurrence of sticky phenomenon when the sheet test piece was peeled from the glass in the same way was observed, and the evaluation was performed using the following criteria.
[0130] As the measuring device, a peel tester adhesion / film lamination peel analysis device (VPA-2: Kyowa Interface Chemical Co., Ltd.) was used.
[0131] 〇: No stick-slip phenomenon occurred (good)
[0132] (※ The amplitude of the adhesive force is less than 30% of the maximum adhesive force)
[0133] ×: Stick-slip phenomenon occurred (bad)
[0134] (2-2) Loss tangent (tanδ)
[0135] Using a viscoelasticity measuring device PHYSICA MCR301 (manufactured by Anton Paar GmbH), a temperature control system CTD450, analysis software Rheoplus, and a geometrically upper and lower grid processed (Japanese: upper and lower lattice processed) parallel plates for measurement.
[0136] Prepare a square sheet test piece of 20 mm × 20 mm and a thickness of 500 μm. Then, clamp this sheet test piece between the plates of the viscoelasticity measuring device at the measurement temperature, and adjust the distance between the plates so that the normal force reaches 0.2 μN. After maintaining the measurement temperature at ±1°C for 2 minutes, set the strain to 1%, the frequency to 100 Hz, the temperature condition to 23°C, and the nitrogen atmosphere.
[0137] Then, set the frequency to a high frequency (100 Hz) for measurement. Under the conditions of logarithmic up and down (Japanese: logarithmic up and down), and the number of measurement points being 5 points / digit, perform dynamic viscoelasticity measurement, thereby measuring the loss tangent (tanδ) of the sheet test piece (especially the adhesive layer), and evaluate it according to the following criteria.
[0138] It should be noted that for the sheet test piece used in this evaluation, the film base material (without demolding treatment) of the sheet sample produced in each experimental example was changed to a film base material with demolding treatment, and an adhesive layer with a thickness of 20 - 25 μm was formed on its demolding treatment surface. In addition, measurement was performed using a product obtained by laminating only this adhesive layer to reach the specified thickness (500 μm) of the sheet test piece.
[0139] 〇: tanδ is 1.26 or less (good)
[0140] ×: tanδ exceeds 1.26 (bad)
[0141] (2-3) Impact resistance test (simple anti-scattering performance test)
[0142] First, a laminate (layer structure of film substrate / adhesive layer / glass plate) was prepared by bonding the sheet samples produced in each experimental example to a glass plate (raw glass) through its adhesive layer. Next, an acrylic block 30 (10 mm in length × 10 mm in width × 10 mm in height) was bonded to the film substrate side of the prepared laminate using a commercially available adhesive 32.
[0143] Then, as Figure 3 shown, the unnecessary parts (film substrate / adhesive layer) around the acrylic block 30 were removed with a knife, thereby obtaining a块状 test piece 50 (acrylic block 30 / adhesive 32 / sheet sample 1a (film substrate 12a / adhesive layer 11a)) on the glass plate 40.
[0144] Then, after leaving the test piece 50 in an environment of 23°C and 50% RH for 5 hours to cure the adhesive 32 in the test piece 50, the块状 test piece 50a after the adhesive was cured was set on Figure 4 the impact test device 60 (Digital impact tester QM 700CA, Qmesys Co., Ltd.) shown. After that, the hammer 62 (load: 273 g) was lifted to a specified angle, and an impact was applied to a part (acrylic block 30) of the test piece 50a. For the test piece 50a, the vertical direction was set as 0 degrees, and the angle when the hammer 62 was lifted counterclockwise was evaluated. The angle when the块状 test piece 50a was peeled off from the glass plate 40 together with the film was evaluated using the following criteria.
[0145] It should be noted that in Figure 4 and 5 , the symbols 64 and 66 are the pressing plate and the fixing table of the glass plate 40 to which the test piece 50a is attached, respectively, and the symbol 68 is the operation panel of the hammer 62.
[0146] ◎: 40 degrees or more (especially good)
[0147] 〇: 35 degrees or more and less than 40 degrees (good)
[0148] ×: less than 35 degrees (bad)
[0149] (2 - 4) Scatter prevention
[0150] The sheet samples produced in each experimental example were bonded to the inner surface of the cover glass of the housing of a smartphone (an example of a mobile device) such that their adhesive layers faced each other, obtaining an evaluation sample (total weight: 130 g) having a structure of glass / adhesive layer / film substrate (laminate of cover glass and scatter prevention sheet).
[0151] Then, after being placed in an environment of 23°C and 50% RH for 30 minutes, the evaluation sample is dropped from a height of about 100 cm from the corner of the evaluation sample at an angle of 45 degrees (colliding with the floor), and this is dropped 10 times. The state of the position where the load is applied is visually confirmed and evaluated using the following criteria.
[0152] ◎: No peeling was observed (0 times / 10 times)
[0153] ○: Almost no peeling (1 to 2 times / 10 times)
[0154] ×: A lot of peeling was observed (more than 3 times / 10 times)
[0155] [Table 1]
[0156]
[0157] 3. Investigation
[0158] As shown in Table 1, the correlation between the occurrence of sticking when the sheet test piece was peeled off from the glass at high speed and the scattering prevention performance was confirmed. That is, when there was a pressure-sensitive adhesive layer that caused sticking during high-speed peeling (Experimental Examples 5 and 6), the scattering prevention performance could not be improved.
[0159] On the other hand, it was confirmed that when the adhesive layer was constructed in a manner that did not cause sticking during high-speed peeling (Experimental Examples 1 to 4), the scattering prevention performance was improved. It was confirmed that when the adhesive layer had a loss tangent (tanδ) at high frequency (100 Hz) adjusted to 1.26 or less (Experimental Examples 1 to 3), the impact resistance and scattering prevention performance were further improved compared to the case where this was not the case (Experimental Example 4).
[0160] Explanation of symbols
[0161] 1…Glass scatter prevention sheet
[0162] 1a…Sheet sample (glass scatter prevention sheet)
[0163] 11, 11a ... adhesive layer
[0164] 12, 12a…film substrate
[0165] 2…Touch panel
[0166] 21…Cover glass
[0167] 22…Transparent conductive film
[0168] 23…Adhesive layer
[0169] 24…Membrane sensor
[0170] 241…Base film
[0171] 242…Transparent conductive film
[0172] 25…Adhesive layer
[0173] 26…Display module
Claims
1. A glass scattering prevention sheet, characterized in that: The invention is a glass scattering prevention sheet which is attached to the cover glass of a mobile device and prevents glass fragments from scattering when the cover glass is broken. The glass scattering prevention sheet includes an adhesive sheet having an adhesive layer composed of an adhesive composition on one surface of a film substrate. The loss tangent tanδ of the adhesive layer at a frequency of 100 Hz is adjusted to be 1.26 or less. Under the environment of temperature 23°C and relative humidity 50%, the adhesive layer of the adhesive sheet was attached to a glass with a thickness of 3 mm using a roller with a load of 2 kgf. After 30 minutes, the adhesive sheet was peeled off from the glass at a speed of 30,000 mm / min in a 180-degree direction. The peeling was performed without causing a stick-slip phenomenon. The stick-slip phenomenon is a phenomenon in which the adhesive force is gradually peeled off while the adhesive force is repeatedly maintained at a certain maximum value for a certain period of time, then the adhesive force is rapidly reduced and then immediately restored, as shown in the adhesive force-peeling time curve when the test is performed under the conditions of the 180-degree peeling adhesive force measurement test on the test plate described in JIS-Z0237. The non-stick-slip phenomenon means that the amplitude of the maximum adhesive force increasing or decreasing by 30% or more does not occur repeatedly more than twice. In addition, when the amplitude of the adhesive force is less than 30%, it is a state of continuous peeling, which is not considered as peeling caused by stick-slip. The loss tangent tan δ is determined as follows: The measurement was performed using a viscoelasticity measuring device PHYSICA MCR301 manufactured by Anton Paar, a temperature control system CTD450, analysis software Rheoplus, and parallel plates with upper and lower grids of φ8 mm in geometry. Prepare a square adhesive layer of 20 mm × 20 mm and 500 μm thick; then, clamp the adhesive layer between the plates of the viscoelasticity measuring device at the measuring temperature, and adjust the distance between the plates so that the normal force reaches 0.2 μN; then, keep the measuring temperature ±1°C for 2 minutes, and set the strain to 1%, frequency to 100 Hz, temperature to 23°C, and nitrogen atmosphere; Then, the frequency was set to a high frequency of 100 Hz for measurement; the dynamic viscoelasticity measurement was performed under the conditions of logarithmic rise and fall and 5 measurement points / digit, thereby measuring the loss tangent tanδ of the adhesive layer, The pressure-sensitive adhesive layer used for measuring the loss tangent tan δ is a pressure-sensitive adhesive layer obtained by laminating pressure-sensitive adhesive layers having a thickness of 20 to 25 μm to a thickness of 500 μm.
2. The sheet according to claim 1, wherein The adhesive composition comprises a crosslinking agent and a (meth)acrylate polymer as a main polymer, The (meth)acrylate polymer includes a structural unit derived from butyl acrylate, a structural unit derived from 2-ethylhexyl acrylate, or both a structural unit derived from butyl acrylate and a structural unit derived from 2-ethylhexyl acrylate.
3. The sheet according to claim 2, wherein: The glass transition temperature Tg of the main polymer is -40°C to -15°C.
4. The sheet according to claim 2 or 3, wherein: The (meth)acrylate polymer includes a structural unit derived from a reactive functional group-containing monomer having a hydroxyl value of 1 mgKOH / g or more and 80 mgKOH / g or less. 5 . The sheet according to claim 1 , further comprising a functional layer having printability on a surface of the film substrate on which the adhesive layer is not formed. 6 . The sheet according to claim 3 , comprising a functional layer having printability on a surface of the film substrate on which the adhesive layer is not formed. 7 . The sheet according to claim 4 , comprising a functional layer having printability on a surface of the film substrate on which the adhesive layer is not formed.
